Echinococcosis: diagnosis and current treatment options - A. N. Lotov; A. V. Chzhao; N. R. Chernaya (Трансплантология (Москва), 2018)
Echinococcosis also remains a serious problem today. Highly informative diagnostic methods allow hepatic echinococcosis to be diagnosed at its early stage. This brings mini-invasive, saving operations under ultrasound, X-ray, TV, and endoscopic guidance up to a new level. The accumulated experience suggests that the current high-tech operations that are an alternative to traditional access surgery can be extensively used. However, only strict observance of a protocol for saving operations, their performance in specialized hospitals, and compulsory antiparasitic therapy with albendazole will be of benefit to mini-invasive surgery for hepatic echinococcosis.